SPECTRAL LUMINOSITY INDICATORS FOR FGKSUPERGIANTS AND CLASSICAL CEPHEIDS - Kovtyukh, V. V.; Chekhonadskikh, F. A. (Одеські астрономічні публікації, 2008)
We have determined 28 relations between M ν, T eff and line depths ratios Rλ1/R λ2. These relations have been used for the estimation of the absolute magnitudes M ν of 56 FGK supergiants with an error 0.05-0.30 mag (Table 1). The application range is F0-K0, luminosity classes I and II.